Intervention of computer-assisted cognitive training combined with occupational therapy in people with mild cognitive impairment: a randomized controlled trial - Wen, Xin; Song, Shangrong; Tian, Hui; Cui, Hang; Zhang, Lijuan; Sun, Yajie; Li, Mingyue; Wang, Yonghong (Frontiers in Aging Neuroscience, 2024)
Objective Investigate the impact of combined computerized cognitive training and occupational therapy on individuals with mild cognitive impairment (MCI). Methods We randomly assigned 118 MCI patients into two groups: a combined intervention group (n=37) and a control group (n=81), the latter receiving standard nursing care. The intervention group additionally underwent 12 weeks of computerized cognitive training and occupational therapy. Blind assessors evaluated cognitive performance, anxiety, depression, and daily living activities before the intervention, post-intervention, and at a 3-month follow-up. Results Repeated-measures analysis of variance showed that the MoCA scores, HAMA scores, and ADL scores of the experimental group at T2 (post-intervention) and T3 (3-month follow-up) were higher than those of the control group, and the difference was statistically significant (P<0.001, P<0.001, P=0.026). Conclusion Computerized cognitive training combined with occupational therapy can improve patients' cognitive status, enhance their compliance with continuing care, and maintain their anxiety and self-care ability at a stable level.